A Sheep in Wolf's Clothing: Listeria innocua Strains with Teichoic Acid-Associated Surface Antigens and Genes Characteristic of Listeria monocytogenes Serogroup 4 - Lan, Zheng (American Society for Microbiology, 2000)
Listeria monocytogenes serotype 4b has been implicated in numerous food-borne epidemics and in a substantial fraction of sporadic listeriosis. A unique lineage of the nonpathogenic species Listeria innocua was found to express teichoic acid-associated surface antigens that were otherwise expressed only by L. monocytogenes of serotype 4b and the rare serotypes 4d and 4e. These L. innocua strains were also found to harbor sequences homologous to the gene gtcA, which has been shown to be essential for teichoic acid glycosylation in L. monocytogenes serotype 4b. Transposon mutagenesis and genetic studies revealed that the gtcA gene identified in this lineage of L. innocua was functional in serotype 4b-like glycosylation of the teichoic acids of these organisms. The genomic organization of the gtcA region was conserved between this lineage of L. innocua and L. monocytogenes serotype 4b. Our data are in agreement with the hypothesis that, in this lineage of L. innocua, gtcA was acquired by lateral transfer from L. monocytogenes serogroup 4. The high degree of nucleotide sequence conservation in the gtcA sequences suggests that such transfer was relatively recent. Transfer events of this type may alter the surface antigenic properties of L. innocua and may eventually lead to evolution of novel pathogenic lineages through additional acquisition of genes from virulent listeriae.